Centralized Big Data Management Model of Object-Oriented Process Driven - Qing Zhang (Dianxin kexue)
Along with big data era,the rapid data growth,large-scale parallel processing and access requirements of increasingly urgent,partition the domain data storage,processing and application architecture has been gradually formed.Enterprises are urgent to achieve full network data integration management,effective data application,guarantee the data quality,give full play to the value of data management.Therefore,a centralized big data management model of object-oriented process driven was proposed.The model uses a life cycle method to tease out several typical data objects,and through a standardized process to drive the collaborative management of data.